2020
DOI: 10.3389/fgene.2020.538640
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Data Provides Novel Insights Into the Genetic Architecture of Meat Quality Traits in Beef

Abstract: Tenderness is a major quality attribute for fresh beef steaks in the United States, and meat quality traits in general are suitable candidates for genomic research. The objectives of the present analysis were to (1) perform genome-wide association (GWA) analysis for marbling, Warner-Bratzler shear force (WBSF), tenderness, and connective tissue using whole-genome data in an Angus population, (2) identify enriched pathways in each GWA analysis; (3) construct a protein-protein interaction network using the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…They provide key insights into the regions that underpin variation in physical meat characteristics, including muscle fibers, connective tissue, IMF, meat color, fat color, shear force, and sensory meat quality traits such as tenderness, juiciness, flavor, chewiness, etc. [ 159 ]. So far, some sensory-related traits including tenderness and color have been confirmed with notable representations of related biomarkers on chromosomes [ 119 ].…”
Section: Main Methods For Measuring and Predicting Beef Qualitymentioning
confidence: 99%
“…They provide key insights into the regions that underpin variation in physical meat characteristics, including muscle fibers, connective tissue, IMF, meat color, fat color, shear force, and sensory meat quality traits such as tenderness, juiciness, flavor, chewiness, etc. [ 159 ]. So far, some sensory-related traits including tenderness and color have been confirmed with notable representations of related biomarkers on chromosomes [ 119 ].…”
Section: Main Methods For Measuring and Predicting Beef Qualitymentioning
confidence: 99%
“…Several of the QTLs for beef colour were confirmed in proteomic studies that identified candidate protein biomarkers (Gagaoua et al, 2020b). On another hand, a recent study focused on Angus examined a range of traits, but their tenderness analysis not only confirmed the known QTLs including the calpain gene, but of the most significant structural genes highlighted in the study, 81% were validated using in silico analysis to be substrates of calpains (Leal-Gutiérrez et al, 2020c), illustrating the central importance of this proteolytic process in defining ultimate beef tenderness. Furthermore, experimental validation of the functional relationship of putative candidate genes with their proposed phenotype is a very valuable addition to GWAS.…”
Section: Genetic Regions and Gene Expression Associated With Meat Qua...mentioning
confidence: 76%
“…Customers’ expectations of meat safety and quality are increasing [ 1 , 2 , 3 , 4 ]. Meat quality is a complex trait that has several defining aspects, such as collagen, water, protein, and fat content, which play critical roles in consumer acceptance and product pricing [ 5 , 6 , 7 ]. Several studies on the meat quality of ducks, especially the fat, protein, collagen, and water content of breast muscle, have been conducted [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%